The Role of Osteopontin and Its Gene on Glucocorticoid Response in Myasthenia Gravis - Xie, Yanchen; Li, Hai-Feng; Sun, Liang; Kusner, Linda L.; Wang, Shuhui; Meng, Yunxiao; Zhang, Xu; Hong, Yu; Gao, Xiang; Li, Yao; Kaminski, Henry J. (Frontiers in Neurology, 2017)
Biomarkers that assess treatment response for patients with the autoimmune disorder, myasthenia gravis (MG) have not been evaluated to a significant extent. We hypothesized the pro-inflammatory cytokine, osteopontin, may be associated with variability of response to glucocorticoids (GCs) in patients with MG. A cohort of 250 MG patients treated with standardized protocol of GCs were recruited, and plasma osteopontin (OPN) and polymorphisms of its gene, secreted phosphoprotein 1 (SPP1) were evaluated. Mean OPN levels were higher in patients compared to healthy controls. Carriers of rs11728697*T allele (allele definition: one of two or more alternative forms of a gene) were more frequent in the poorly GC responsive group compared to the GC responsive group indicating an association of rs11728697*T allele with GC non-responsiveness. One risk haplotype (AGTACT) was identified associated with GC non-responsiveness compared with GC responsive MG group. Genetic variations of Spp1 was found associated with the response to GC among MG patients.